The Un-Freud, for Better or Worse - Emma Lieber (EJP import test, 2019)
Summary: “The Uncanny” begins with Freud’s admission that he doesn’t know much about the subject: he is not prone to the uncanny feeling. He is also not prone, he says, to writing about art and literature, since “it is only rarely that a psychoanalyst feels impelled to investigate the subject of aesthetics.” Except, all the evidence speaks to the contrary: writings on Dostoevsky, on Leonardo, on Jensen’s “Gradiva,” on Michelangelo’s Moses, on Hamlet, The Merchant of Venice, King Lear, and Macbeth, on Goethe’s Dichtung und Wahrheit, on fairy tales, on mythology, and, in “The Uncanny,” on E.T.A. Hoffman’s “The Sand Man.” So why, in “The Uncanny,” in which the uncanny feeling and the aesthetic are so closely aligned, does Freud exclude himself from both? Mladen Dolar writes that in his investigation of the uncanny, “Freud is gradually forced to use the entire panoply of psychoanalytic concepts” such that “one could simply say that it is the pivotal point around which psychoanalytic concepts revolve.” The uncanny, as code for psychoanalysis itself, is in Freud’s essay further linked not only to aesthetics, but also to castration, femininity, interiority, and domesticity; and to writing. This paper will examine this complex in the essay to pose a question about the position, ignorance, and exclusion of the analyst, and about what it means to write as a psychoanalyst.
Keywords: Feminine; literature; resistance; uncanny; writing